Authority of Notary to Make Roya Concent as in Literature Certificate of Loss - Aditya Rahma Wicaksono; Lathifah Hanim; Soegianto Soegianto (Sultan Agung Notary Law Review, 2020)
This study aims to determine and analyze the authority of the notary in making Roya's Concentration Deed and to find out the stages in making the Roya Concentration Deed as a substitute for the lost certificate of mortgage. The approach method in this research uses juridical empiric. The specification of this research is descriptive analysis, the data required includes primary data, secondary data, and tertiary data, the data analysis method uses field research and library research. Based on the research, it is concluded that although the Roya concession deed or the Roya license deed is not clearly regulated, it is related to the authority of the notary in making the deed, because if it is linked in the Roya process to be carried out at the Land Office, the Roya Consent Deed is one of the requirements for implementing Roya. Roya's consent deed is a notary deed that has a position as a substitute for a lost certificate of mortgage, which functions as a condition for registering Roya or withdrawing mortgage rights. Roya consent deed or Roya permit is also a type of partij deed which is a notary made at the request of the parties concerned by accompanying evidence of a letter of loss from the police regarding the loss of a certificate of mortgage, the notary makes a deed of Roya/consent Roya permit to fulfill formal functions a deed, namely to complete or complete a legal act in this case to Roya at the Land Office.